1992
DOI: 10.1007/bf01321285
|View full text |Cite
|
Sign up to set email alerts
|

Use of mental health services among severely emotionally disturbed children and adolescents in San Francisco

Abstract: This study examined the mental health services available to severely emotionally disturbed children and adolescents in San Francisco. Social, familial, developmental, and clinical data---as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
(12 reference statements)
3
11
0
Order By: Relevance
“…This compares well with the findings of Barber et al (1992), who reported a mean age of 12 years for boys and 13 years for girls in a community sample, and to the findings of Singh et al (1994), who reported a mean age 14^ JOURNAL OF EMOTIONAL AND of 11.6 years in an inpatient psychiatric hospital sample. However, regional and other factors could be operating with respect to the average age at which services are provided.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This compares well with the findings of Barber et al (1992), who reported a mean age of 12 years for boys and 13 years for girls in a community sample, and to the findings of Singh et al (1994), who reported a mean age 14^ JOURNAL OF EMOTIONAL AND of 11.6 years in an inpatient psychiatric hospital sample. However, regional and other factors could be operating with respect to the average age at which services are provided.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, boys with SED outnumbered girls with SED by 4:1. This finding is consistent with estimates of the prevalence of SED (Kauffman, 1993) as well as with the findings in studies of children with SED in inpatient psychiatric hospitals (Sinclair, Forness, & Alexon, 1985;Singh et al, 1994) and in community programs (e.g., Barber et al, 1992). It is interesting that Barber et al reported that this ratio decreases with age: They found that the boy to girl ratio changed from 4:1 in preadolescents to 3:2 in adolescents.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations